The legal orthopedia of human dignity: Thinking with Axel Honneth. (October 2014) - Mendieta, Eduardo
This article develops a constructivist, non-metaphysical, non-essentialist conception of human dignity using Jeremy Waldron, Michael Rosen, Ernst Bloch, Jürgen Habermas and Axel Honneth. This constructivist conception of dignity is then related to the communicative or reflexive conception of freedom developed by discourse ethics. Then, these two conceptions are demonstrated to be foundational for the development and implementation of human rights.